2022
DOI: 10.1186/s12916-022-02521-y
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a digital medication event reminder and monitor device for patients with tuberculosis (SELFTB): a multicenter randomized controlled trial

Abstract: Background Tuberculosis remains the leading cause of death from a single infectious disease worldwide. Trials evaluating digital adherence technologies for tuberculosis in low- and middle-income countries are urgently needed. We aimed to assess whether a digital medication event reminder and monitor (MERM) device-observed self-administered therapy improves adherence and treatment outcomes in patients with tuberculosis compared with the standard in-person directly observed therapy (DOT). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…A clinically diagnosed case of TB was also not documented among enrolled patients, possibly reflecting the ingrained thinking of health workers that associates TB with a cough lasting longer than 2 weeks. The wider clinical, public health, social and structural forces are all important in decisions surrounding TB screening, diagnosis, and management [34] , [35] , [36] , [37] , [38] , [39] .…”
Section: Discussionmentioning
confidence: 99%
“…A clinically diagnosed case of TB was also not documented among enrolled patients, possibly reflecting the ingrained thinking of health workers that associates TB with a cough lasting longer than 2 weeks. The wider clinical, public health, social and structural forces are all important in decisions surrounding TB screening, diagnosis, and management [34] , [35] , [36] , [37] , [38] , [39] .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies also used complementary measures such as pill counts, self report by persons on treatment, or urine tests. [17,23,31] Most suggested that the use of the pillboxes was associated with improved adherence.…”
Section: Adherencementioning
confidence: 99%
“…The implementation of systematic screening of TB in high-burden countries is influenced by multiple factors, including low screening and testing capacity, limited understanding of systematic screening techniques, and limited health workers’ competence in TB screening. 19 24 The characteristics of technological innovations and advancements, access, sensitivity, and specificity of chest X-ray techniques facilitate, while cost and providers’ lack of technical competency hinder, the adoption of chest X-rays in systematic TB screening. 25 29 …”
Section: Introductionmentioning
confidence: 99%